2018
DOI: 10.1007/s11207-018-1289-2
|View full text |Cite
|
Sign up to set email alerts
|

Automated Identification of Coronal Holes from Synoptic EUV Maps

Abstract: Coronal holes (CH) are regions of open magnetic field lines in the solar corona and the source of fast solar wind. Understanding the evolution of coronal holes is critical for solar magnetism as well as for accurate space weather forecasts. We study here the extreme ultraviolet (EUV) synoptic maps at three wavelengths (195Å/193Å, 171Å and 304Å) measured by Solar and Heliospheric Observatory/Extreme Ultraviolet Imaging Telescope (SOHO/EIT) and Solar Dynamics Observatory/Atmospheric Imaging Assembly (SDO/AIA) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…The changes in the CH area, shown in Figure , have a similar trend as the observed CH changes shown in Figure 3 in Lowder et al () and Figure 10 in Hamada et al (). For example, the results shown in Figure with the PFSS model and those in Lowder et al () and Hamada et al () obtained using images of the solar corona agree that northern and SP CHs show asymmetric evolution and a time lag between their formation. This should not be confused with periodic variations of the CH area in the polar regions which are caused by the lack of their coverage due to the tilt of the Sun's axis with respect to the ecliptic plane.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The changes in the CH area, shown in Figure , have a similar trend as the observed CH changes shown in Figure 3 in Lowder et al () and Figure 10 in Hamada et al (). For example, the results shown in Figure with the PFSS model and those in Lowder et al () and Hamada et al () obtained using images of the solar corona agree that northern and SP CHs show asymmetric evolution and a time lag between their formation. This should not be confused with periodic variations of the CH area in the polar regions which are caused by the lack of their coverage due to the tilt of the Sun's axis with respect to the ecliptic plane.…”
Section: Resultssupporting
confidence: 83%
“…Since the interplanetary magnetic field represents the coronal magnetic field which is carried out by the solar wind, this implies a complex dependence of regions which are the source of the solar wind on solar activity. It is known from observations of the solar corona that CHs, which are a source of solar wind and interplanetary magnetic field, change in size and location as the solar cycle progresses (see, e.g., Hamada et al, , Harvey & Recely, , Lowder et al, , ). During the solar minimum, they occupy large polar regions of the Sun, while during the period of high solar activity usually smaller CHs appear at the lower latitudes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synoptic maps provide a convenient way to display the evolution and/or distribution of various physical quantities and features on the entire solar surface. For example, synoptic maps have been used to study coronal holes (CH) (Karna et al, 2015;Golubeva and Mordvinov, 2017;Hamada et al, 2018), photospheric and coronal magnetic fields (Virtanen and Mursula, 2016), and long-lived active regions (ARs). Solar synoptic maps can also be used to study the nonuniform structure of the EUV corona in both longitude and latitude, reflecting the nonuniform distribution of the large-scale magnetic field (Benevolenskaya, Kosovichev, and Scherrer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The convection effect by high-speed SW is the likely source of the strong periodicity in cosmic rays. Lowder et al (2017) and Hamada et al (2018) found a difference in the evolution of northern and southern CHs during the SC 23 and SC 24. In Interval B the polar CHs were not as large as in Interval A, but there were low-latitude CHs (Figure 10), even with transequatorial extensions (e.g., Dunzlaff et al, 2008;Gómez-Herrero et al, 2009), which caused the narrow peak in power spectrum density of 27.5 days in GCR.…”
Section: Discussionmentioning
confidence: 94%